Stress and Coping Strategies Amongst Islamic Education Novice Teachers - Tengku Kasim, Tengku Sarina Aini; Abdul Majid, Azizah (Jurnal Usuluddin, 2020)
Studies have shown that teaching profession is considered to be a highly stressful career and this can lead to teachers suffering from burnout. Teachers from many countries reported high levels of stresses, particularly, novice teachers who seem to be more vulnerable to the pressures of the profession compared to experienced teachers. Thus, in order to fill in the voids in the existing teacher stress literature, the present study aims to investigate factors contributing to stress among Islamic Education novice teachers during their early years of teaching and their coping strategies to minimize the pressure. This study was conducted on a number of Islamic education novice teachers in secondary schools from four different states in Malaysia. The data were acquired by using semi-structured individual interviews. Insight into these factors and coping strategies can serve as significant guidance in laying out support for novice teachers’ professional development.